Menyongsong masa depan: Kewirausahaan dan ekonomi digital dalam perspektif Pancasila - Udin, Ahmad Irfan; Prasrtyo, Yogi; Rifansyah, Nauval Annafi (Maliki Interdisciplinary Journal, 2024)
Pancasila as the ideology of the Indonesian nation functions as a foundation for Indonesian citizens in all aspects of life, including in implementing entrepreneurship and running the digital economy. Facing the future by adhering to the principles of Pancasila should be a subject of study so that our nation becomes a country based on Pancasila, not only from a theoretical perspective, but also prioritizing practice in social and state life.